Kompetensi Profesional Pendidik Menurut Al-Ghazali - Ismatul Maula (Oasis : Jurnal Ilmiah Kajian Islam, 2020)
Competence is the initial basis for a teacher to carry out his duties in teaching, but today many teachers do not understand the importance of a competency. Many of those who teach are limited to fulfilling their obligations without considering competency aspects which are the basic foundation in learning. al-Ghazali as a figure in Islamic education contributed a lot of thought in the world of education, among which he was concerned with the components of teachers and students. In thinking about the teacher he discussed in the book of IhyÄ â€˜UlÅ«m al-AddÄ«n Volume 1 Chapter al-â€˜Ilm. Al-Ghazali explained how educator professional competence must be possessed before carrying out teaching assignments. The problem of this research is "What is the professional competence of educators according to al-Ghazali" ?. So from that the purpose of this study was to find out the professional competence of educators according to al-Ghazali.Â Kompetensi adalah dasar awal bagi seorang guru untuk melaksanakan tugasnya dalam mengajar, akan tetapi dewasa ini banyak guru yang tidak memahami arti penting sebuah kompetensi. Banyak dari mereka yang mengajar hanya sebatas menunaikan kewajiban tanpa mempertimbangkan aspek kompetensi yang merupakan landasan dasar dalam pembelajaran. al-Ghazali sebagai tokoh pendidikan Islam banyak menyumbangkan pemikiran dalam dunia pendidikan, diantara yang menjadi perhatian beliau adalah pada komponen guru dan siswa. Dalam pemikiran mengenai guru yang beliau membahasnya dalam kitab IhyÄ â€˜UlÅ«m al-AddÄ«n Jilid 1 Bab al-â€˜Ilm. Al-Ghazali menjelaskan bagaimana kompetensi profesional pendidik yang harus dimiliki sebelum melakukan tugas mengajar. Yang menjadi permasalahan dari penelitian ini adalah â€œBagaimana kompetensi profesional pendidikmenurut al-Ghazali?â€. Maka dari itu tujuan dari penelitian ini adalah untuk mengetahui kompetensi profesional pendidik menurut al-Ghazali.Â